2014
DOI: 10.1002/hipo.22319
|View full text |Cite
|
Sign up to set email alerts
|

PTU‐induced hypothyroidism in rats leads to several early neuropathological signs of Alzheimer's disease in the hippocampus and spatial memory impairments

Abstract: The multifactorial causes impacting the risk of developing sporadic forms of Alzheimer's disease (AD) remain to date poorly understood. Epidemiologic studies in humans and research in rodents have suggested that hypothyroidism could participate in the etiology of AD. Recently, we reported that adult-onset hypothyroidism in rats favors β-amyloid peptide production in the hippocampus. Here, using the same hypothyroidism model with the antithyroid molecule propythiouracyl (PTU), we further explored AD-related fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 81 publications
7
39
0
Order By: Relevance
“…Similar to previous findings, the fall in THs associated with elevated TSH, GH and IGF-II [47,48]. The elevated TNF-ɑ level indicated an increase in proinflammatory cytokine release in hypothyroidism [49].…”
Section: Discussionsupporting
confidence: 88%
“…Similar to previous findings, the fall in THs associated with elevated TSH, GH and IGF-II [47,48]. The elevated TNF-ɑ level indicated an increase in proinflammatory cytokine release in hypothyroidism [49].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study in rats indicated that adult hypothyroidism might be a risk factor for the development of dementia and Alzheimer's disease [48]. TH insufficiency, even for a short period, might cause irreversible brain damage [49] and extensively elicits OE degeneration in rodents [39,50].…”
Section: Discussionmentioning
confidence: 99%
“…This last action is related (again) to changes in the hippocampus [164] . These experimental findings are of interest to our research because they correlate with the effects of thyroid function on the hippocampus [165] , [166] , [167] , [168] as well as to psychological stress due to trauma [46] , [134] , [169] , [170] . As a corollary of these data we propose that magnesium deficiency could be involved in altered cognition development, an issue that has been seen almost exclusively to be related to thyroid function.…”
Section: Discussionmentioning
confidence: 99%